Investigation of Aerodynamic Parameters on Small Horizontal Axis Wind Turbine Blade at Low Wind Speeds - (:unkn) unknown (Chennai, 2023)
In this research work, the investigation and optimization of newlinesmall horizontal axis wind turbine blade at low wind speed is pursued. newlineThe airfoil E210, NACA2412, S1223, SG6043, E216, NACA4415, newlineSD7080, SD7033, S1210 and Four new airfoil Series (MKC, NAF, newlineMAF and AF) were tested at the wind speed of 2-6 m/s. An X-Foil and newlineCFD software were used to devise a novel airfoil MKC, NAF, MAF and newlineAF suitable for use at low Reynolds number. In this study, an optimized newlinedesign method based on BEM Theory is explained blade radius of 0.2 m newlineto 0.5 m rotors investigated with and without winglet blade geometry of newlinemore than 100 Low Reynolds number airfoil. The initial experiment newlinecovered a wide range of tip speed ratios, ranging from 3 to 10, solidity newlineranges from 0.0431 0. 286 and angle of attacks from 2o to 20o.The newlinepower coefficient, lift coefficient, drag coefficient, and lift to drag ratio newlinewere later optimized and investigated using MATLAB and X-Foil newlinesoftware. It is noted that by changing the blade geometry from constant newlinev newlinechord and non-twisted to variable chord and twisted blade geometry at and#963; newline= 0.055, there was a 28.26 % and a 21.42 % increase in maximum Cp newlinebetween blade number, B = 3 and B = 6. However, for B = 3 and B = 6, newlineconstant chord geometry for blade design, it is noted that by changing newlinethe blade geometry from constant chord and non-twisted to variable newlinechord and twisted blade geometry at solidity, and#963; = 14 %, there was a newline34.88 % and a 33.33% increase in maximum Cp between blade number, newlineB = 3 and B = 6. The experimental blades were created utilizing the newlineadditive manufacturing process of 3D printing. At various wind speeds, newlinesingle and multistage rotors are explored. newlineThe investigations of the efficiency of the rotors has been done in newlinean open wind tunnel, at blade angles of 15o, 30o and 45o. The airfoil newlineNACA, SG, E and S series airfoil were selected for the design of the newlinesingle-airfoil blades tested at the rated wind speed of 6 m/s. The various newlineairfoil were investigated with the aid of the X-Foil software at Reynolds newlinenumbers of
Keywords: Engineering; Engineering and Technology; Engineering Mechanical